Methyl Jasmonate Regulates Antioxidant Defense and Suppresses Arsenic Uptake in Brassica napus L. - Farooq, Muhammad A.; Gill, Rafaqat A.; Islam, Faisal; Ali, Basharat; Liu, Hongbo; Xu, Jianxiang; He, Shuiping; Zhou, Weijun (Frontiers in Plant Science, 2016)
Methyl jasmonate (MJ) is an important plant growth regulator, involved in plant defense against abiotic stresses, however its possible function in response to metal stress is poorly understood. In the present study, the effect of MJ on physiological and biochemical changes of the plants exposed to arsenic (As) stress were investigated in two Brassica napus L. cultivars (ZS 758 – a black seed type, and Zheda 622 – a yellow seed type). The As treatment at 200 µM was more phytotoxic, however its combined application with MJ resulted in significant increase in leaf chlorophyll fluorescence, biomass production and reduced malondialdehyde content compared with As stressed plants. The application of MJ minimized the oxidative stress, as revealed via a lower level of reactive oxygen species (ROS) synthesis (H2O2 and OH-) in leaves and the maintenance of high redox states of glutathione and ascorbate. Enhanced enzymatic activities and gene expression of important antioxidants (SOD, APX, CAT, POD), secondary metabolites (PAL, PPO, CAD) and induction of lypoxygenase gene suggest that MJ plays an effective role in the regulation of multiple transcriptional pathways which were involved in oxidative stress responses. The content of As was higher in yellow seeded plants (cv. Zheda 622) as compared to black seeded plants (ZS 758). The application of MJ significantly reduced the As content in leaves and roots of both cultivars. Findings of the present study reveal that MJ improves ROS scavenging through enhanced antioxidant defense system, secondary metabolite and reduced As contents in both the cultivars.